Information-Based Approaches of Noninvasive Transcranial Brain Stimulation. Issue 11 (November 2016) - Romei, Vincenzo; Thut, Gregor; Silvanto, Juha
Abstract : Progress in cognitive neuroscience relies on methodological developments to increase the specificity of knowledge obtained regarding brain function. For example, in functional neuroimaging the current trend is to study the type of information carried by brain regions rather than simply compare activation levels induced by task manipulations. In this context noninvasive transcranial brain stimulation (NTBS) in the study of cognitive functions may appear coarse and old fashioned in its conventional uses. However, in their multitude of parameters, and by coupling them with behavioral manipulations, NTBS protocols can reach the specificity of imaging techniques. Here we review the different paradigms that have aimed to accomplish this in both basic science and clinical settings and follow the general philosophy of information-based approaches. Trends: Conventional use of noninvasive transcranial brain stimulation (NTBS) in the study of perception and cognition involves enhancing or disrupting behavior, aiming to map cortical regions to behavioral functions. Novel NTBS paradigms aim to understand how information related to perceptual and cognitive processes is represented by neural networks, mirroring the general philosophy of theinformation-based approach in functional neuroimaging. This is achieved by manipulations of stimulation parameters and prior/concurrent task demands to target specific neural networks or populations.